Transboundary water disputes : state conflict and the assessment of their adjudication / Itzchak E. Kornfeld. - Kornfeld, Itzchak E. (Cambridge University Press, 2019)
One of the most challenging aspects of climate change has been the increased pressure on water resources limited by droughts and new rain patterns, which has been exacerbated by rapid modernization. Due to these realities, disputes across national borders over use and access to water have now become more commonplace. This study analyzes the history and adjudication of transboundary water disputes in five international courts and tribunals, two US Supreme Court cases, and boundary water disputes between the United States and Canada and the United States and Mexico. Explaining the circumstances and outcomes of these cases, Kornfeld asks how effective the courts and tribunals have been in adjudicating them. What kind of remedies have they fashioned and how have they dealt with polycentric and sovereignty issues? This timely work examines the doctrine of equitable allocation of transboundary water resources and how this norm can be incorporated into international law.